Penerapan Metode Model View Controller dan Clustering Untuk Sistem Pemesanan Menu Berbasis Android - Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Waroenk Akul is a variety of food places located in the Pasar Minggu area of ​​South Jakarta, where Waroenk Akul is still applying the method of ordering food directly to the seller by means of the customer getting a menu book and recording the desired menu order still using the books and pens provided, based on the application. android here this ordering aims to make it easier for customers to order and choose food using their respective customer's cellphones, this android feature is also available a menu that is often ordered by customers in its android application. In this research, the system development uses the MVC (Model View Controller) method which divides the login display and the user interface or the display seen by the user, while the Clustering searches for information data in a system, with a key, for example finding the fried rice menu, then will appear all types of fried rice menu. With this system, it is very easy for customers to see the food menu without having to open the book food menu.